Ethnic differences in beta-cell function, dietary intake and expression of the metabolic syndrome among UK adults of South Asian, black African-Caribbean and white-European origin at high risk of metabolic syndrome. - Goff, L; Griffin, B; Lovegrove, J; Sanders, T; Jebb, SA; Bluck, L; Frost, G (2013)
A cross-sectional analysis of ethnic differences in dietary intake, insulin sensitivity and beta-cell function, using the intravenous glucose tolerance test (IVGTT), was conducted on 497 healthy adult participants of the 'Reading, Imperial, Surrey, Cambridge, and Kings' (RISCK) study. Insulin sensitivity (Si) was significantly lower in African-Caribbean (AC) and South Asian (SA) participants [IVGTT-Si; AC: 2.13 vs SA: 2.25 vs white-European (WE): 2.84 (×10(-4) mL µU min)(2), p < 0.001]. AC participants had a higher prevalence of anti-hypertensive therapy (AC: 19.7% vs SA: 7.5%), the most cardioprotective lipid profile [total:high-density lipoprotein (HDL); AC: 3.52 vs SA: 4.08 vs WE: 3.83, p = 0.03] and more pronounced hyperinsulinaemia [IVGTT-acute insulin response (AIR)] [AC: 575 vs SA: 428 vs WE: 344 mL/µU/min)(2), p = 0.002], specifically in female participants. Intake of saturated fat and carbohydrate was lower and higher in AC (10.9% and 50.4%) and SA (11.1% and 52.3%), respectively, compared to WE (13.6% and 43.8%, p < 0.001). Insulin resistance in ACs is characterised by 'normal' lipid profiles but high rates of hypertension and pronounced hyperinsulinaemia.